Aleijão: a desconstrução na poesia do tempo presente - Oliveira, Samanta Barreto Matos (2017)
The present dissertation proposes to analyze the book Aleijão (2009), by the Brazilian poet Eduardo Sterzi (Porto Alegre, 1973). This analysis of the poems and the structure of Aleijão aims to identify and discuss the elements that constitute the poetry that can, from the structural and thematic elements, lead to represent the condition of a fragmented contemporary man. It is assumed that this work exemplifies contemporary issues, bringing its vision of a world that is not welcoming, violent, and offers only the disturbing vision of chaos. There are in the verses expressions of aggressiveness, presented explicitly or in ironic suggestions ("This corpse is ours / lunch / What will be the dessert?"), bringing metaphors of passivity and accommodation in the face of violence and death dealt with by the poetic self with naturalness in front of grotesque images. And, parallel to the images, fragmentary syntactic procedures emphasize, in the language itself, the fragmentation condition of contemporary man. As the dissertation sought to discuss, such aspects focus on Sterzi's poetry revealing the deconstruction of the poetic making of the present time